2019
DOI: 10.1016/j.nicl.2019.101911
|View full text |Cite
|
Sign up to set email alerts
|

Selective hippocampal subfield volume reductions in classic trigeminal neuralgia

Abstract: Trigeminal Neuralgia (TN) is a chronic neuropathic pain syndrome characterized by paroxysmal unilateral shock-like pains in the trigeminal territory most frequently attributed to neurovascular compression of the trigeminal nerve at its root entry zone. Recent advances in the study of TN suggest a possible central nervous system (CNS) role in modulation and maintenance of pain. TN and other chronic pain patients commonly experience alterations in cognition and affect, as well as abnormalities in CNS volume and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
47
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 63 publications
5
47
0
2
Order By: Relevance
“…This study revealed a bilateral decrease of the GM volume in the hippocampus after 3 months of HF‐10 SCS. Reductions in hippocampal GM have previously been demonstrated in different chronic pain populations 44–46 . Moreover, these results are in line with the study of Luchtmann et al, 47 who demonstrated a decreased hippocampal volume in patients suffering from chronic low back pain after microsurgical lumbar discectomy.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This study revealed a bilateral decrease of the GM volume in the hippocampus after 3 months of HF‐10 SCS. Reductions in hippocampal GM have previously been demonstrated in different chronic pain populations 44–46 . Moreover, these results are in line with the study of Luchtmann et al, 47 who demonstrated a decreased hippocampal volume in patients suffering from chronic low back pain after microsurgical lumbar discectomy.…”
Section: Discussionsupporting
confidence: 87%
“…Reductions in hippocampal GM have previously been demonstrated in different chronic pain populations. [44][45][46] Moreover, these results are in line with the study of Luchtmann et al, 47 who demonstrated a decreased hippocampal volume in patients suffering from chronic low back pain after microsurgical lumbar discectomy. It might be suggested that treatment could reverse the previously occurring neuroplastic changes due to the presence of chronic pain.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Within them, LC had four regions decreased in nodal efficiency after acupuncture. The cingulum hippocampus, which was the essential structure with the limbic system, was related to cognitive impairment and emotional change on trigeminal neuralgia and chronic pain patients [47].…”
Section: Discussionmentioning
confidence: 99%
“…PTSD (Bøen et al, 2014;Chen et al, 2016;Averill et al, 2017;Hayes et al, 2017), childhood maltreatment (Teicher et al, 2012;Chalavi et al, 2015), verbal abuse , childhood trauma in schizophrenia and healthy controls (du Plessis et al, 2019), in bipolar disorders and healthy controls (Janiri et al, 2019a) and in adolescence (Malhi et al, 2019) Other neuropsychiatric conditions Pain symptoms (Ezzati et al, 2014), ADHD (Al-Amin et al, 2018), anorexia nervosa (Myrvang et al, 2018), obsessive compulsive disorder (Zhang et al, 2019), and transient global amnesia (Wang et al, 2018b), essential tremor (Prasad et al, 2019), rapid eye movement sleep behavior disorder (Campabadal et al, 2019), trigeminal neuralgia (Vaculik et al, 2019) Thalamic infarction (Chen et al, 2016), sequelae of microsurgical aneurysm clipping (Hedderich et al, 2019)…”
Section: Posttraumatic Stress Disorder (Ptsd) and Early Life Adversitymentioning
confidence: 99%